The Linkage Between Innovative Human Resource Practices And Perceived Organizational Support - Wahab, Eta; Kah Chun, Yip (Research in Management of Technology and Business, 2021)
This study attempts to investigate the relationship between innovative human resource practices and perceived organizational support among employees. The objectives of this research are to identify the level of innovative human resource practices (IHRP) among employees, to determine the level of perceived organizational support (POS) among employees and to study the relationship between innovative human resources practices (IHRP) and perceived organizational support (POS) among employees. Quantitative approach had been used in this study and a survey had been conducted among 382 employees from banking services sector companies in Kuala Lumpur with a response rate of 48.95%. Online survey had been employed in this study. The data collected had been analysed using descriptive analysis and correlation analysis. The result shows a medium level of IHRP and high level of POS. The result also shows that there is a significant relationship between innovative HR practices and perceived organizational support in this study.